REPORT OF THE 1957 PRESIDENT. - Moyer, C. A. (The Accounting Review, 1958)
Abstract A report of the activities of the American Accounting Association for 1957 offers problems similar to those encountered in accounting for inventories and for cost of goods finished in a manufacturing concern. The purpose of this report is to furnish the membership with a brief description of what the Association is doing and some of its plans for the future. The primary emphasis by the Association over its life has been on accounting education and accounting research although other accounting areas are not neglected. This continuing emphasis on education and research is quite apparent in the description which follows. The Committee on Accounting Concepts and Standards completed its revision of the 1948 version of Accounting Concepts and Standards Underlying Corporate Financial Statements. The quarterly publication "The Accounting Review," has continued to expand and improve over the years, and has become recognized throughout the world as a leading accounting periodical. During the year hundreds of individuals who receive it, including many not engaged in teaching, have complimented the Association on the quality of the content of this publication.